Risk factors associated with multidrug-resistant Klebsiella pneumoniae infections: a multicenter observational study in Lebanese hospitals - Rania Itani; Hani M. J. Khojah; Rahaf Kibrit; Hamza Raychouni; Patricia Shuhaiber; Carole Dib; Mariam Hassan; Tareq L. Mukattash; Abdalla El-Lakany (BMC, 2024)
Abstract Background Klebsiella pneumoniae is a significant global public health burden, especially in low-income countries and regions with fragile healthcare infrastructures, due to its ability to cause severe infections, increase mortality rates, and its rising antimicrobial resistance. This study aimed to estimate the proportion of multidrug-resistant (MDR) K. pneumoniae infections and identify associated risk factors. Methods Data were retrospectively collected from three academic hospitals in Beirut, Lebanon, between January 2021 and September 2023 using a standardized form. Binary logistic regression was used to determine risk factors associated with MDR, extended-spectrum beta-lactamase (ESBL)-producing, and carbapenem-resistant K. pneumoniae (CRKP) infections. Results Out of 2,655 K. pneumoniae cases, 410 met the inclusion criteria. The primary infection sources were the urinary tract (58.3%) and the respiratory tract (12.4%). Among the isolates, 61% were MDR K. pneumoniae, with 7.3% being extensively drug-resistant, and 0.5% pandrug-resistant. Additionally, 36.8% were ESBL-producing, while 6.3% were CRKP. Predictors significantly associated with MDR K. pneumoniae infections included male sex (adjusted odds ratio [AOR] = 3.46, 95% CI = 1.01-11.86, P = 0.04), recent antibiotics use (AOR = 4.52, 95% CI = 1.65-12.36, P = 0.003), and recent cancer chemotherapy (AOR = 3.43, 95% CI = 1.25-9.42, P = 0.01). ESBL-producing infections were associated with age ≥ 65 years, higher Charlson Comorbidity Index (CCI), and recent antibiotic use. CRKP infections were linked to male sex, prior antibiotic use, and longer hospital stays prior to infection (all P < 0.05). Conclusions MDR K. pneumoniae infections are steadily rising in Lebanon, along with an increase in ESBL-producing and CRKP cases. The main risk factors for MDR K. pneumoniae infections were male sex, recent antibiotic use, and cancer chemotherapy. ESBL-producing infections were associated with advanced age, higher CCI, and recent antibiotic use, while CRKP infections were linked to male sex, prior antibiotic use, and prolonged hospital stays. This situation is further exacerbated by inadequate healthcare infrastructure and suboptimal national surveillance. Strengthening local surveillance and implementing effective antibiotic stewardship programs are critical to managing this growing threat..